Ultralow-power adiabatic circuit semi-custom design. - Blotti, A. (IEEE Transactions on VLSI systems)
This brief shows that a conventional semi-custom design-flow based on a positive feedback adiabatic logic (PFAL) cell library allows any VLSI designer to design and verify complex adiabatic systems (e.g., arithmetic units) in a short time and easy way, thus, enjoying the energy reduction benefits of adiabatic logic. A family of semi-custom PFAL carry lookahead adders and parallel multipliers were designed in a 0.6-μm CMOS technology and verified. Post-layout simulations show that semi-custom adiabatic arithmetic units can save energy a factor 17 at 10 MHz and about 7 at 100 MHz, as compared to a logically equivalent static CMOS implementation. The energy saving obtained is also better if compared to other custom adiabatic circuit realizations and maintains high values (3÷6) even when the losses in power-clock generation are considered.